The American Horseshoe Crab (Limulus polyphemus) - Savanna Barry; Holly Abeels; Shelly Krueger (EDIS, 2020)
American horseshoe crabs (Limulus polyphemus) look prehistoric and in fact really have not changed very much in the 200 million years they have been around. This 3-page fact sheet written by Savanna Barry, Holly Abeels, and Shelly Krueger and published by the UF/IFAS Program in Fisheries and Aquatic Sciences, School of Forest Resources and Conservation tells the story of these interesting and valuable "living fossils," including their importance both to ecology and human medicine. It provides tips on how to find horseshoe crabs and a few ways you can help them.